The Figino, or On the Purpose of Painting : Art Theory in the Late Renaissance - Comanini, Gregorio, -1608 (Book collections on Project MUSE., 2001)
Of the many treatises written in Italy during the Counter-Reformation, none is more illustrative of the intellectual fermentation of the period than Comanini's work on the purpose of painting, Il Figino overo del fine della Pittura (1591). Although the importance of Il Figino has long been recognized, the text has remained largely inaccessible to many scholars throughout the world. This first complete English translation will make the work available to those readers for the first time. In Il Figino, Comanini addresses all of the most hotly debated aesthetic issues of the time, drawing on an array of classical, medieval and Renaissance sources, including Plato, Aristotle, Horace, Mazzoni, Tasso and Paleotti. The editor and translator provide copious notes which clarify Comanini's aesthetic and theological references, as well as a lucid introduction that places the issues and debates in context. Comanini's impressive erudition makes his treatise an excellent barometer of the state of scholarship in the Counter-Reformation era. This translation is a long-overdue addition to the field of Renaissance studies.